(untitled) (mathematica didactica, 2024)
Understanding and using the language of mathematics coherently is a challenge for many freshmen. So far, however, there is little evidence on students’ written use of the language of mathematics. This paper presents an inventory that was conducted in an Analysis 1 course. As part of the study, exercises of 15 students were qualitatively evaluated in a cross-sectional and longitudinal study. The results show a great variety of expressions, e.g. on implications, and an increasing sovereignty in the use of the language of mathematics during the course.